Analisis Kesalahan Penggunaan Kata “Chadianr” dan “Chabuduo” pada Mahasiswa Angkatan 2023 Prodi Pendidikan Bahasa Mandarin Universitas Tanjungpura - Uray Ridha Amalia; Tjen Veronica; Bun Yan Khiong (Cerdika: Jurnal Ilmiah Indonesia, 2026)
Vocabulary is a fundamental component in language learning because it plays a role as a basis for forming sentences and conveying meaning. In learning Chinese, the use of vocabulary that has similar meanings (synonyms) often causes errors, especially in the pairs of words "chadianr" and "chabuduo" which in Indonesian are both interpreted as "almost", but have different uses in Chinese. This study aims to analyze the misuse of the vocabulary "chadianr" and "chabuduo" in students of the 2023 batch of the Chinese Language Education Study Program, Tanjungpura University. This study uses a quantitative method with a data collection technique in the form of a test consisting of 30 questions, namely 15 multiple-choice questions and 15 true-false questions, which were given to 42 respondents. The data is analyzed descriptively by calculating the percentage of errors and classifying the types of errors that arise. The results showed that the error rate of using "chadianr" was 21.02% and "chabuduo" was 29.77%, with the more dominant error occurring in the use of "chabuduo". The types of errors found include substitution errors and sequence errors. The factors that cause errors come from negative interference of the first language and negative interference of the target language knowledge. Based on these results, it can be concluded that although some students have understood the use of both vocabulary, there are still errors that show the need to improve understanding of the difference in meaning and the use of synonymous vocabulary in Chinese